Strategic management accounting and information technology competency on customer service process performance in local government agencies / Jamaliah Said ... [et al.] - Said, Jamaliah; Wee, Shu Hui; Othman, Rohana; Taylor, Dennis (Universiti Teknologi MARA Cawangan Selangor, 2012)
The main objective of this study is to examine the effects of the adoption of Strategic Management Accounting (SMA) techniques and Information Technology (IT) competency on customer service process performance of Malaysian Local Government Agencies (LGA). Questionnaires were mailed to top managers of all 146 LGAs. The findings revealed that SMA information use and IT competency contribute directly in improving reliability of service delivery, level of staff responsiveness in attending to customers’ issues and requests, staff competency in carrying out tasks, and staff skills in providing service at a faster rate with less error. The results therefore suggest that IT competency adds value to LGAs that use SMA information via its ability to store, retrieve and process information with speed and accuracy. IT competency enables LGAs to provide online transactions, thereby facilitating revenue collection and reducing uncollected revenue while the use of SMA techniques can help LGAs to eliminate non-value added activities.